Privilege-seeking activities in organizational politics and its effect on more productive employees - Gil S. Epstein; Bruce C. Herniter (Bar-Ilan University, Department of Economics, 2011)
The ability to accurately evaluate an employee would seem to be a key activity in managing Information Technology (IT). Yet, workers may engage in dishonest and misleading behavior, which distort the evaluation, a variation of organizational politics. Why would they do so? One hypothesis is that privilege-seeking, that is, managing one's managers (also called rentseeking, management relations, or organizational politics), can be used by a worker to misrepresent his actual contribution. These activities lead to a reduction in productivity and consequently to a loss of profits. Management may decrease the firm's losses by engaging in costly monitoring activities. It is paradoxical that a behavior with such negative consequences is tolerated. A model is developed to show that an organization should be composed of employees with different levels of productivity; moreover, it may be optimal for the organization to have some employees who are good at privilege-seeking activities, forcing the remaining workers to invest in productive activities. This contradicts existing theory that unequal compensation should be less motivating and the remaining workers less productive.
Keywords: 330; employee evaluation; equity theory; influence costs; management relations; multiple agent model; monitoring; Nash equilibrium; privilege-seeking activities; rent; rent-seeking; Arbeitsproduktivität; Personalbeurteilung; Rationales Verhalten; Rent-Seeking; Nash-Gleichgewicht; Agentenbasierte Modellierung; Theorie